Therapeutic Efficacy of Melatonin in Patients with Coronavirus 2019: A Systematic Review and Meta-Analysis of Randomized Controlled Trials : - Akbari , Maryam; Bagheri Lankarani , Kamran; Homayounfar, Reza; Tabrizi , Reza; Vali , Mohebat; Zakeri , Mohamad- Reza; Farjam, Mojtaba; Khodadost, Mahmoud; Ahmadizar , Fariba (Galen Medical Journal, 2022)
The efficacy of melatonin in the treatment of patients with coronavirus 2019 (COVID-19) is controversial. This review has summarized the evidence on the efficacy of oral melatonin compared to placebo in patients with mild to moderate COVID-19 infection. We searched four international online databases and all randomized clinical trials (RCTs) that investigated the effects of melatonin compared with the placebo on clinical outcomes, including mortality, discharge time, O2 saturation (SaO2), and c-reactive protein (CRP) levels in patients with COVID-19 infection, were included. The standard random-effects model with hybrid continuity correction was used to pool the risk ratio (RR), weighted mean difference (WMD), and the I2 index to assess the heterogeneity. A total of 272 patients from five RCTs were included. Our meta-analysis showed melatonin compared to placebo, decreased discharge time (WMD=-0.93 days; 95% confidence interval [CI]:-2.94 to 1.07, P=0.36; I2=56.78%) and the risk of mortality (RR=0.72; 95% CI:0.25 to 2.13, P=0.56; I2=0.0%) in COVID-19 patients. Melatonin intake compared to placebo significantly increased SaO2 (WMD=1.38%; 95% CI:0.09 to 2.68, P=0.04; I2=49.82%) and decreased the CRP levels (WMD=-7.24 mg/l; 95% CI:-11.28 to -3.21, P<0.001) in a sensitivity analysis. Our findings showed the efficacy of melatonin compared to placebo in patients with mild to moderate COVID-19 infection.